Rule of law versus political interest - Saltman, Michael (Contemporary crises, 1990)
The limits of the rule of law are here tested by a case study. Two Arab prisoners were killed by Israeli security forces, a political cover-up was initiated and the tacit assent of the Supreme Court towards executive actions was achieved. The paper examines some theoretical positions in order to understand the relationship between the ideology of the Rule of Law and political interests — Althusser, Luhmann and Habermas. The conclusion is that structural and/or neo-structural functional theory is insufficient to explain the situation. The paper suggests alternative variables to account for the legal system's subservience to the dictates of political interests.